Doxxing as a Cybersecurity Threat: A Systematic Review - Anti, Emmanuel; Dang, Duong; Vartiainen, Tero (Association for Information Systems, 2026)
Doxxing, the intentional public disclosure of personal information, has been widely examined as privacy violation, cyberbullying, and digital vigilantism, yet its cybersecurity implications remain underdeveloped. This study addresses that gap through a systematic review and interpretive coding of 34 peer-reviewed articles. The findings support a four-stage socio-technical escalation pathway comprising exposure, enrichment, exploitation, and systemic impact. The model explains how doxxing evolves through interactions among stakeholders, platform affordances, and governance constraints, enabling social engineering, impersonation, and broader organizational and societal harm without traditional system intrusion. The study extends cybersecurity research and highlights intervention points for threat modeling, organizational preparedness, and governance coordination.
Keywords: Doxxing; Cybersecurity; Threats; Socio-Technical Systems; fi=Viestintätieteet|en=Communication Studies|; fi=Tietojärjestelmätiede|en=Information Systems Science|